Optical Coherence Tomography Detection of Neurodegeneration in Multiple Sclerosis - Lidster, Katie; Baker, David (CNS & Neurological Disorders - Drug Targets, 2012)
The pathophysiology of multiple sclerosis (MS) is typically characterised by inflammation and demyelination leading to neurodegeneration, which is associated with disability and the progressive stages of MS. The visual system is a valuable tool for studying neurodegeneration and potential neuroprotection in the central nervous system due to its ease of accessibility. Optical coherence tomography (OCT) is a non-invasive tool, which can be used to measure the thickness of the retinal nerve fibre layer (RNFL). The thickness of RNFL is reduced following the development of MS and optic neuritis and can therefore be used as a correlate of global axonal loss. OCT is currently being investigated as a structural outcome measure for neuroprotective clinical trials of MS. This review describes the relationship between MS and optic neuritis and the associated RNFL thinning, the technology and advancements of OCT, the role of OCT in clinical trials for new neuroprotective therapies in MS and the future role of OCT in MS research.
Keywords: Spectral domain optical coherence tomography